CLINICAL AND DERMOSCOPIC CHARACTERISTICS OF ACTINIC KERATOSIS AT THE NATIONAL HOSPITAL OF DERMATOLOGY AND VENEREOLOGY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the general characteristics, clinical features, and dermoscopic findings of actinic keratosis (AK) in patients presenting to the National Hospital of Dermatology and Venereology.Materials and Methods: A cross‑sectional descriptive study was conducted on 57 patients with 105 clinically diagnosed AK lesions at the National Hospital of Dermatology and Venereology from August 2024 to August 2025. Data on age, sex, lesion location and morphology, symptoms, and dermoscopic features were collected. Selected lesions were biopsied for histopathological correlation.Results: The mean age was 71.9 ± 13.9 years; the male/female ratio was approximately 1:2. A total of 105 lesions were recorded, predominantly located on the head and face (about 92.4%), most frequently on the cheeks, followed by the nose. Most lesions were isolated (98.1%) with a mean area of 1.2 ± 0.5 cm². Lesions of moderate thickness accounted for 74.3%, whereas very thick lesions represented only 7.6%. 52.4% case reported pruritus , while 47.6% were completely asymptomatic. Clinically, the classic AK subtype predominated (91.4%), with cutaneous horn and pigmented variants accounting for 1.0% and 7.6%, respectively. On dermoscopy, non‑pigmented AK lesions showed a typical “strawberry pattern” in 78.1%. All eight pigmented AK lesions had a rough, scaly surface and exhibited a brown pseudonetwork with polygonal lines and an annular–granular pattern. Other dermoscopic features, including marked scaling, white structureless areas, rosettes, and dotted, glomerular, hairpin and polymorphous vessels, were observed with low frequencies.Conclusion: In this cohort, actinic keratosis mainly affected elderly patients, chronic sun exposure, with lesions predominantly located on the head and face. The “strawberry pattern” in non‑pigmented AK and the pigmented pseudonetwork with an annular–granular pattern in pigmented AK were the most characteristic dermoscopic features.
Keywords: Actinic keratosis; Dermoscopy; Strawberry pattern